Model Laporan Keuangan Sederhana Dengan Menggunakan Aplikasi Android Akuntansi UKM Pada UKM di Kabupaten Brebes - Nurul Mahmudah; Yusri Anis Faidah (Faculty of Economics and Business, University of Pancasakti Tegal, 2022)
The more advanced development of Indonesia is expected to be in line with the existence of economic development in terms of small micro and medium enterprises. This cannot be denied by the growing development of various types of small and medium enterprises in Indonesia, especially in Central Java. One of many government's efforts is to increase income in that aim to improve the welfare of society, the role of UKM is very much needed with the development of UKM in Central Java, especially in Brebes district. It is proving that the domestic market share ranging from low to medium-sized economies can be absorbed. One of the problems faced by UKM is preparing simple financial reports. It is because UKM is required to be able to understand simple financial reports systematically, the existence of an android application model